2015
DOI: 10.1080/03632415.2015.1017635
|View full text |Cite
|
Sign up to set email alerts
|

Reservoir Rehabilitations: Seeking the Fountain of Youth

Abstract: Aging of reservoirs alters the functions, and associated services, of these systems through time. The goal of habitat rehabilitation is often to alter the trajectory of the aging process such that the duration of the desired state is prolonged. There are two important characteristics in alteration of the trajectory—the amplitude relative to current state and the subsequent rate of change, or aging—that ultimately determine the duration of extension for the desired state. Rehabilitation processes largely fall i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 22 publications
(19 reference statements)
0
15
0
Order By: Relevance
“…, Pegg et al. ). In these particular circumstances, the detection of a hump‐shaped pattern will be very unlikely because the depression phase will be replaced by a plateau or a slow decreasing trend in abundance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…, Pegg et al. ). In these particular circumstances, the detection of a hump‐shaped pattern will be very unlikely because the depression phase will be replaced by a plateau or a slow decreasing trend in abundance.…”
Section: Discussionmentioning
confidence: 99%
“…Reservoir management actions such as fish stocking, fishing, and mitigation measures could also alter population trajectories and affect our ability to detect the TS. For example, one mitigation measure applied in some reservoirs is to add nutrients in the reservoir to delay the depression phase (Agostinho et al 1999, Pegg et al 2015. In these particular circumstances, the detection of a hump-shaped pattern will be very unlikely because the depression phase will be replaced by a plateau or a slow decreasing trend in abundance.…”
Section: Variation In the Trophic Surgementioning
confidence: 99%
See 1 more Smart Citation
“…Degradation of shorelines and nearshore areas through erosion, sedimentation, loss of submerged structure, and widespread substrate homogenization over time can decrease habitat complexity and is a common concern for reservoir managers (Allen and Aggus ; Miranda and Krogman ; Pegg et al. ). Decreasing habitat complexity can negatively affect fish communities (e.g., alter species composition and abundance), can reduce recruitment of fish species that support key recreational fisheries (Smokorowski and Pratt ; Carmignani and Roy ), and results in low species diversity in structurally simple mudflats (Hatcher et al.…”
mentioning
confidence: 99%
“…It has long been conjectured that reservoirs differ in the chronological rate at which they manifest senescence (Pegg et al 2015), but so far no attempt has been made to find an indicator that performs better than years since impoundment. In gerontology and related fields, the term "functional age" has been used as a descriptive label for research efforts that have suggested that functional capabilities are likely to be more meaningful than mere chronological age for characterizing the senescing status of an individual.…”
Section: Discussionmentioning
confidence: 99%